Longitudinal Moderated Mediation Analysis in Parallel Process Latent Growth Curve Modeling in Intervention Studies. Issue 3 (May 2021) - Zhu, Shijun; Sagherian, Knar; Wang, Yan; Nahm, Eun-Shim; Friedmann, Erika
Abstract : Background: Intervention studies are used widely in nursing research to explore the efficacy of intervention programs for changing targeted health outcomes. However, the analyses of such studies have focused predominantly on their main intervention effects; most studies ignore the mechanisms underlying how the intervention programs work partly because of lack of application details of the longitudinal mediation analysis techniques. Objectives: The aim of this study was to illustrate an application of parallel process latent growth curve modeling (PP-LGCM) to examine longitudinal moderated mediation effects. Methods: Longitudinal data from an online bone health intervention study were used to demonstrate the step-by-step application of PP-LGCM with Mplus statistical software. Results: With modification indices, we were able to achieve adequate model fit for PP-LGCM in our data. The mediation effects of self-efficacy on the intervention effects on exercise were nonsignificant for the entire sample. However, the conditional indirect effect showed the mediation effects were moderated by age group. Discussion: PP-LGCM provides an efficient way to analyze and explain the underlying mechanisms for the intervention effects in a trial, especially when the intervention program is guided by a theory. Abstract : Supplemental digital content is available in the text.